Analysis of The Effect of Digital Marketing, Product Innovation and Market Orientation on Marketing Performance through Competitive Advantage as an Intervening Variable (Case Study of Coffee Shop at Medan) (International Journal of Economics and Management Research, 2026)
This study aims to analyze the effect of digital marketing, product innovation and market orientation on marketing performance through competitive advantage as an intervening variable. The method used is causal associative research with a quantitative approach, which aims to examine the relationship between one or more variables with a research population of 78 respondents. The data analysis technique used is Structural Equation Modeling with Partial Least Square (SEM-PLS). The results showed that digital marketing and market orientation have a direct effect on competitive advantage, while product innovation has no effect on competitive advantage. Digital marketing has no effect on marketing performance, while product innovation and market orientation have a direct effect on marketing performance. Path analysis shows that the combination of digital marketing and product innovation has an insignificant impact on marketing performance, indicating that competitive advantage has not been able to mediate the relationship between digital marketing and product innovation.